The language myth why language is not an instinct - Evans, Vyvyan (Cambridge, United Kingdom Cambridge University Press, 2014)
"Language is central to our lives, the cultural tool that arguably sets us apart from other species. Some scientists have argued that language is innate, a type of unique human 'instinct' pre-programmed in us from birth. In this book, Vyvyan Evans argues that this received wisdom is, in fact, a myth. Debunking the notion of a language 'instinct', Evans demonstrates that language is related to other animal forms of communication; that languages exhibit staggering diversity; that we learn our mother tongue drawing on general properties and abilities of the human mind, rather than an inborn 'universal' grammar; and that, ultimately, language and the mind reflect and draw upon the way we interact with others in the world. Compellingly written and drawing on cutting-edge research, The Language Myth sets out a forceful alternative to the received wisdom, showing how language and the mind really work"--Provided by publisher.
Acknowledgements -- 1. Language and mind rethought -- 2. Is human language unrelated to animal communication systems? -- 3. Are there language universals? -- 4. Is language innate? -- 5. Is language a distinct module in the mind? -- 6. Is there a universal Mentalese? -- 7. Is thought independent of language? -- 8. Language and mind regained.
Includes bibliographical references (pages 274-300) and index.
Keywords: Linguistic universals; Cognitive grammar; Innateness hypothesis (Linguistics).; Language and languages -- Philosophy; Psycholinguistics